PENGARUH SEDIMETASI PADA KINERJA PENGOPERASIAN WADUK SERBAGUNA WONOGIRI - Hana Umayektinisa; Niken Ajeng S.P.; Suharyanto Suharyanto; Sumbogo Pranoto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
The operation of the reservoir can’t be avoided from the problem of sedimentation. This happens because the natural ingredients in the river sediment transport will be accommodated and deposited in the reservoir due to the dam. But not all the sediment deposited in the reservoirs will go straight into the dead storage, most of the sediment will be deposited on effective storage. Has been a lot of research and efforts to reduce the influence of reservoir sedimentation. However, little (if any) research on the effect of reservoir sedimentation in reservoir operation performance. In a study on the effect of sedimentation on the operating performance of single-purpose dam sedimentation concluded that the effect was not significant. Therefore, in this study conducted research on the effect of sedimentation in the multipurpose reservoir operational performance. This research was conducted by simulating the operation of reservoirs with different patterns of operation and conditions of sedimentation.